Analysis of supervised classification techniques - Lakhmi Prasanna, P.; Rajeswara Rao, D.; Meghana, Y.; Maithri, K.; Dhinesh, T. (International Journal of Engineering and Technology, 2017)
As the number of digital documents and data are being increased rapidly, it is important to classify them in to respective categories. This process of classifying the data is called classification. There are three ways in to which the data can be classified un supervised, supervised and semi supervised methods. Automatic Text Classification is done by supervised learning techniques. This paper discusses about various classification techniques, their advantages and limitations. Finally, it concludes with the best classification technique. In this paper the best classification technique that was proposed is Artificial Neural Network (ANN). The reason for proposing ANN as the best algorithm is given and its application in various important fields was given.